The roles of adhesion, internal heat generation and elevated temperatures in normally loaded, sliding rough surfaces. (1st March 2020) - Poole, Benjamin; Barzdajn, Bartosz; Dini, Daniele; Stewart, David; Dunne, Fionn P.E.
Highlights: Temperature rises due to plastic and heat generation are inconsequential when sliding rates representative to galling are accounted for. The strength of adhesion is not relevant to the deformation of rough surfaces in the context of single-phase austenitic 316L stainless steel during metal-on-metal contact. Increasing temperatures show quantifiable effects on galling resistance but not to the level as found experimentally in the literature. Galling appears to be controlled by mechanisms (e.g. phase transformation, surface coating degradation) other than the simple mechanisms considered here. Abstract: The thermal effects of plastic and frictional heat generation and elevated temperature were examined along with the role of adhesion in the context of galling wear, using a representative crystal plasticity, normally loaded, sliding surface model. Galling frequency behaviour was predicted for 316L steel. Deformation of the surfaces was dominated by the surface geometry, with no significant effect due to variations in frictional models. Plastic and frictional heating were found to have a minimal effect on the deformation of the surface, with the rapid conduction of heat preventing any highly localised heating. There was no corresponding effect on the predicted galling frequency response. Isothermal, elevated temperature conditions caused a decrease in galling resistance, driven by the temperature sensitivity of the critical resolved shear stress. The extent of deformation, as quantified by the area of plastically deformed material and plastic reach, increased with temperature. Comparisons were made with literature results for several surface amplitude and wavelength conditions. Model results compared favourably with those in the literature. However, the reduction in predicted galling resistance with elevated temperature for a fixed surface was not as severe as observations in the literature, suggesting other mechanisms (e.g. phase transformations, surface coatings and oxides) are likely important.